The Effectiveness of Mental Health Rehabilitation Services: A Systematic Review and Narrative Synthesis - Dalton-Locke, Christian; Marston, Louise; McPherson, Peter; Killaspy, Helen (Frontiers in Psychiatry, 2021)
Introduction: Mental health rehabilitation services provide essential support to people with complex and longer term mental health problems. They include inpatient services and community teams providing clinical input to people living in supported accommodation services. This systematic review included international studies evaluating the effectiveness of inpatient and community rehabilitation services. Methods: We searched six online databases for quantitative studies evaluating mental health rehabilitation service that reported on one or both of two outcomes: move-on to a more independent setting (e.g. discharge from an inpatient unit to the community or from a higher to lower level of supported accommodation); inpatient service use. The search was further expanded by screening references and citations of included studies. Heterogeneity between studies was too great to allow meta-analysis and therefore a narrative synthesis was carried out. Results: We included a total of 65 studies, grouped as: contemporary mental health rehabilitation services (n=34); services for homeless people with severe mental health problems (n=13); deinstitutionalisation programmes (n=18). The strongest evidence was for services for homeless people. Access to inpatient rehabilitation services was associated with a reduction in acute inpatient service use post discharge. Fewer than one half of people moved on from higher to lower levels of supported accommodation within expected timeframes. Conclusions: Inpatient and community rehabilitation services may reduce the need for inpatient service use over the long term but more high quality research of contemporary rehabilitation services with comparison groups is required. Review registration: This review was prospectively registered on PROSPERO (ID: CRD42019133579).